2022
DOI: 10.5812/mejrh-118587
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Quality of Life and Coping Strategies in Hospitalized Patients with COVID-19

Abstract: Background: The COVID-19 pandemic may have destructive effects on patients’ mental health and quality of life (QoL). Objectives: This study aimed to assess the relationship between QoL and coping strategies in hospitalized patients with COVID-19. Methods: This cross sectional descriptive-analytical study was performed at Imam Reza Hospital in Tabriz City for 2 months. Seventy hospitalized patients with COVID-19 were recruited by convenience sampling. The patients completed the adapted version of the World Heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…Our findings corroborate existing literature indicating the positive association between the use of problem-focused coping and QOL pre-pandemic [ 47 49 ] and during the pandemic [ 28 , 34 , 35 ]. On the other hand, previous research, most of which was conducted pre-pandemic, has demonstrated inconsistent findings regarding the relationship between emotion-focused coping and QOL, with many studies pointing to a negative association between these two constructs [ 47 , 49 , 50 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings corroborate existing literature indicating the positive association between the use of problem-focused coping and QOL pre-pandemic [ 47 49 ] and during the pandemic [ 28 , 34 , 35 ]. On the other hand, previous research, most of which was conducted pre-pandemic, has demonstrated inconsistent findings regarding the relationship between emotion-focused coping and QOL, with many studies pointing to a negative association between these two constructs [ 47 , 49 , 50 ].…”
Section: Discussionsupporting
confidence: 91%
“…A large-scale study [ 33 ] in the United Kingdom found that emotion-focused coping strategies were more likely to be used when individuals experienced financial stressors (i.e., their or their partner’s loss of employment or inability to work, decrease in household income) or worries about contracting or becoming severely sick from COVID-19 and that both problem-focused coping and avoidant coping strategies were likely to be employed when respondents reported adverse financial events as well as worries about finances, basic needs, or contracting COVID-19. In terms of potential links between coping and QOL during the pandemic, research [ 34 ] has shown that for patients hospitalized with COVID-19, the use of problem-focused coping mechanisms had a direct and positive correlation with their QOL. Additionally, Quiroga-Garza et al [ 35 ] found that problem-focused and emotion-focused coping were marginally, but significantly, correlated with well-being.…”
Section: Introductionmentioning
confidence: 99%